Pengaruh Model Team Game Tournament (TGT) Berbasis Kearifan Lokal dalam Pembelajaran Materi Virus terhadap Peningkatan Hasil Belajar Siswa Kelas X MA Nurul Huda Kragan - Astarinah, Ayu (Pendidikan Biologi Universitas PGRI Ronggolawe Tuban, 2024)
This study aims to analyse the effectiveness of Team Game Tournament (TGT) learning model based on local wisdom in improving student learning outcomes on virus material in class X MA Nurul Huda Kragan. This research uses the Classroom Action Research (PTK) method carried out in two cycles, with qualitative and quantitative approaches. The research subjects were 30 students who were selected based on the results of the initial observation of the achievement of the Minimum Completeness Criteria (KKM). The results showed that the application of the TGT model was able to significantly improve teacher and student activities. Teacher activities increased from 96% in cycle I to 100% in cycle II, while the average student learning outcomes increased from 76.30 to 78.67. The decrease in standard deviation from 7.29 to 5.50 also showed more even learning outcomes. The integration of local wisdom, such as traditional medicine and local endemic disease issues, made learning more contextual and relevant. These findings indicate that the local wisdom-based TGT model is effective in improving learning outcomes, active student involvement, and fostering a more meaningful and applicable understanding of biology concepts. This model can be an alternative strategy that answers the challenges of 21st century learning.